Farmer's Perception on Climatic Factors and Social-economic Characteristics in the Agricultural Sector of Gujarat - Singh, Ajay K.; Ashraf, Shah Nawaz; Sharma, Sandeep Kumar (Research on World Agricultural Economy, 2023)
This study investigated the implication of various factors, including climatic conditions, social-economic variables, agricultural inputs, technological development, institutional support, and adaptation strategies in the agricultural sector of Gujarat. A confirmatory factor analysis (CFA) was used to analyse the farm-level data from 240 randomly selected farmers across eight districts. The study found that farm income per hectare is influenced by climate adaptation strategies, appropriate technology, annual income, education level, family size, fertilizer application, farm income from cash crops, financial support from the government, and access to credit. The study recommends the use of appropriate technology and adaptation strategies to mitigate the negative impact of climate change, as well as increase farmers' access to credit, diversify crops, and encourage technological development in the agricultural sector. In addition, agricultural extension and development agencies should train farmers regularly to improve their understanding of climate adaptation practices and other inputs. ER